The impact of oral nutrition in patients after radical cystectomy: an overview. Issue 3 (6th September 2017) - Villa, Giulia; Bresciani, Martina; Boarin, Mattia; Manara, Duilio F.
ABSTRACT: Nutritional status is considered a significant factor determining the post‐operative outcomes after RC. The aim of this literature review is to describe the impact of early oral nutrition on functional outcomes in patients underwent cystectomy. Usually, these patients are not fed orally until the return of gastrointestinal function, because early oral nutrition is often perceived as detrimental for the anastomosis integrity and is believed to cause nausea and vomiting. This phase of nutritional deprivation may vary from a few days to a few weeks, depending on the return of bowel movements. In clinical practice, patients are fed on a substitutive nutritional support based on the use of total parenteral nutrition or enteral nutrition, which have not demonstrated positive effects on bowel function recovery time, infection complication rates or length of hospital stay. The early introduction of oral feeding seems to allow early mobilization and to lead to an improvement of post‐operative outcomes: bowel functions, pain, complications, patient's comfort and length of hospital stay. The early implementation of oral diet after cystectomy is associated with an improvement of considered outcomes, allowing an early recovery of patient's general conditions and reducing length of hospital stay.